Strategic Management Practices of PT Bank Central Asia Tbk: Navigating Challenges and Leveraging Opportunities in Indonesia's Banking Sector - , Kalfin; Yuningsih, Siti Hadiaty; Halim, Nurfadhlina Abdul (International Journal of Research in Community Services, 2024)
This paper provides an in-depth analysis of strategic management practices employed by PT Bank Central Asia Tbk (BCA), one of Indonesia's leading banks. The study investigates BCA's strategic initiatives across multiple dimensions including organizational strategy, competitive positioning, customer service enhancement, digital transformation, and sustainability efforts. Through a strategic management lens, the analysis examines how BCA has navigated challenges and capitalized on opportunities in the dynamic banking landscape of Indonesia. Key strategic decisions, such as market segmentation, product innovation, and technology adoption, are explored to understand their impact on BCA's market leadership and financial performance. Additionally, the paper discusses the role of corporate governance and leadership in driving BCA's strategic objectives forward.